Measurement of the inclusive charmless and double-charm B branching ratios - Abreu, P; Adam, W; Adye, T; Adzic, P; Alekseev, G; Alemany, P; Allport, P; Almehed, S; Amaldi, U; Amato, S; Andersson, P; Andreazza, A; et al. (1998)
The DELPHI experiment at LEP has measured the inclusive charmless B hadron decay branching ratio, the B branching ratio into two charmed particles, and the total number of charmed particles per B decay, using the hadronic Z data taken between 1992 and 1995. The results are extracted from a fit to the b-tagging probability distribution based on the precise impact parameter measurements made using the microvertex detector. The inclusive charmless B branching ratio, including B decays into hidden charm (cc̄), is measured to be 0.033 ± 0.021. The B branching ratio into two open charmed particles is 0.136 ± 0.042. The mean number of charmed particles per B decay (including hidden charm) is 1.147 ± 0.041. After subtracting the B decay branching ratio into hidden charm, the charmless B branching ratio is found to be 0.007 ± 0.021, compatible with the Standard Model expectation. Models that predict an additional contribution to the charmless B branching ratio of 0.037 or higher are excluded with at least 95% confidence. © 1998 Elsevier Science B.V. All rights reserved.